OpenGL programming for Windows 95 and Windows NT - Fosner, Ron (Addison-Wesley Developers Press, 1996)
The licensing of OpenGL to many leading computer companies, including Microsoft, has made it possible for graphics programmers to learn to write stunning 3D graphics programs using the industry graphics standard on the world's most popular operating system. And OpenGL Programming for Windows 95 and Windows NT is the key to the door of opportunity for those who see the tremendous potential for programmers who can produce high-quality 3D applications on these platforms. Using numerous examples, Microsoft's Visual C++ programming platform, the C++ programming language, and the Microsoft Foundation Classes, Fosner starts with a generic C application that can be compiled from any 32-bit C compiler and, step by step, covers the basics of creating an OpenGL program: Selecting the appropriate pixel format Arranging the device context and rendering contexts Enhancing OpenGL programs to achieve maximum speed Using display lists and texture maps Finding OpenGL enhancements hidden in your video driver Programming OpenGL's Modelview matrix to get the effects you want Providing rapid animation under Windows -- without bogging down the user interface. Most important, you'll absorb this knowledge within the context of developing a Windows application that you can experiment with and actually use in your Windows programs. You will gain hands-on experience in designing, creating, programming, measuring, and optimizing a real OpenGL 3D animation program.